A territorialidade judaica em Santa Maria/RS: uma contribuição à geografia cultural - Santos, Maria Medianeira dos (2009)
The process of construction of the State's territory, as well as of its cultural identity is related to the influence that the several migration flows had in elapsing of time, in the southern space of RS. It is emphasized that this work focuses the Jewish cultural group. This ethnic group penetrated, in 1904, in the territory of the Municipal district of Santa Maria/RS, and they were the responsible for the formation of the Philippson's Colony. As specific objective the research sought: (a) to analyze the responsible conditions for the (de- and re-) territorialization of the Jewish cultural group, in Santa Maria's territory, in the beginning of the 20th century; (b) to verify the aspects of the re-territorialization which provided the formation of the Philippson's Colony/Santa Maria, for the Jews in the State; and (c) to identify the process and the dynamics of the territorial development of Philippson, as well as the space dispersion of the Jews in the urban environment. Methodologically, it was taken a theoretical referential as start point, turned to the thematic in evidence and, in a second moment, field work took place. As to territorial development of Philippson, it can be said that, initially, the rural space was destined for the Jews. However, the territorial dynamics performed by them, culminated with the abandonment of the agricultural activities and in their turn to the urban environment of Santa Maria, in which they were devoted, the great majority, to the commercial area. As to the materialization of the Jewish culture, that can be visualized in Santa Maria's urban landscape through the Synagogue Yitzhak Rabin, the house of Jacob established on Rio Branco Avenue, the Israeli cemetery, located in the neighborhood Chácara das Flores, and moreover, the Jewish cemetery in the municipal district of Itaara.